KEWENANGAN TENTARA NASIONAL INDONESIA (TNI) DALAM PEMBERANTASAN TINDAK PIDANA TERORISME - Nadya Azzahra; Syamsir Syamsir; Muhammad Amin (Universitas Jambi, Fakultas Hukum, 2022)
Abstract The authority of the Indonesian National Armed Forces (TNI) in eradicating criminal acts of terrorism in an effort to maintain the sovereignty of the Republic of Indonesia has been explicitly regulated in several laws and regulations. As regulated in Law Number 3 of 2002 concerning National Defense, Law Number 34 of 2004 concerning the Indonesian National Army, and Law Number 5 of 2018 concerning Eradication of Criminal Acts of Terrorism. However, in the implementation of the law relating to the involvement of the TNI in eradicating acts of terrorism as mandated in Article 341 of Law Number 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism, it has not been authorized in a concrete way because it is constrained by the formation of a Presidential Regulation as an implementing regulation. The involvement of the Indonesian National Army has not been completed so far, so that the involvement of the Indonesian National Army (TNI) in combating acts of terrorism is still in the nature of assistance to the National Police Institution through State Political Policy, and the position of the Indonesian National Army is the main component in the State defense system as mandated in Law Number 3 of 2002 concerning National Defense in the context of carrying out defense tasks in Indonesia. Keywords: Authority, TNI, Terrorism Abstrak Kewenangan Tentara Nasional Indonesia (TNI) dalam pemberantasan tindak pidana terorisme dalam upaya menjaga kedaulatan NKRI secara eksplisit telah diatur dalam beberapa peraturan perundang-undangan. Seperti diatur di dalam Undang-Undang Nomor 3 Tahun 2002 tentang Pertahanan Negara, UndangUndang Nomor 34 Tahun 2004 tentang Tentara Nasional Indonesia, dan Undang undang Nomor 5 Tahun 2018 tentang Pemberantasan Tindak Pidana Terorisme. Namun, dalam penerapan Undang-undang yang berkaitan dengan pelibatan TNI dalam pemberantasan aksi terorisme sebagaimana amanat pada pasal 341 Undang-undang Nomor 5 Tahun 2018 tentang Pemberantasan Tindak Pidana Terorisme, belum dapat di kewenangan secara konkret di lapangan karena terkendala oleh pembentukan Perpres sebagai aturan pelaksanaan pelibatan Tentara Nasional Indonesia yang belum rampung sampai saat ini, sehingga pelibatan Tentara Nasional Indonesia (TNI) dalam pemberantasan aksi terorisme masih bersifat perbantuan terhadap Institusi Polri melalui Kebijakan Politik Negara, dan Kedudukan Tentara Nasional Indonesia merupakan komponen utama dalam sistem pertahanan Negara sesuai yang diamanatkan dalam Undang-Undang Nomor 3 Tahun 2002 tentang Pertahanan Negara dalam rangka melaksanakan tugas-tugas pertahanan di Indonesia. Kata Kunci : Kewenangan, TNI, Terorisme